Relative sarcopenia and mortality and the modifying effects of chronic kidney disease and adiposity. Issue 2 (19th February 2019) - Ziolkowski, Susan L.; Long, Jin; Baker, Joshua F.; Chertow, Glenn M.; Leonard, Mary B.
Abstract: Background: Conventional definitions of sarcopenia based on lean mass may fail to capture low lean mass relative to higher fat mass, that is, relative sarcopenia. The objective of this study is to determine the associations of sarcopenia and relative sarcopenia with mortality independent of co‐morbidities, and whether chronic kidney disease (CKD) and adiposity alter these associations. Methods: Dual energy X‐ray absorptiometry‐derived appendicular lean mass index (ALMI, kg/m 2 ) and fat mass index (FMI, kg/m 2 ) were assessed in 14 850 National Health and Nutrition Examination Survey participants from 1999 to 2006 and were linked to death certificate data in the National Death Index with follow‐up through 2011. Sarcopenia was defined using sex‐specific and race/ethnicity‐specific standard deviation scores compared with young adults (T‐scores) as an ALMI T‐score < −2 and relative sarcopenia as fat‐adjusted ALMI (ALMIFMI ) T‐score < −2. Glomerular filtration rate (GFR) was estimated using creatinine‐based (eGFRCr ) and cystatin C‐based (eGFRCys ) regression equations. Results: Three (3.0) per cent of National Health and Nutrition Examination Survey participants met criteria for sarcopenia and 8.7% met criteria for relative sarcopenia. Sarcopenia and relative sarcopenia were independently associated with mortality (HR sarcopenia 2.20, 95% CI 1.69 to 2.86; HR relative sarcopenia 1.60, 95% CI 1.31 to 1.96). The corresponding population attributable risks were 5.2% (95% CI 3.4% to 6.4%) and 8.4% (95% CI 4.8% to 11.2%), respectively. Relative sarcopenia remained significantly associated with mortality (HR 1.32, 95% CI 1.08 to 1.61) when limited to the subset who did not meet the criteria for sarcopenia. The risk of mortality associated with relative sarcopenia was attenuated among persons with higher FMI ( P for interaction <0.01) and was not affected by CKD status for either sarcopenia or relative sarcopenia. Conclusions: Sarcopenia and relative sarcopenia are significantly associated with mortality regardless of CKD status. Relative sarcopenia is nearly three‐fold more prevalent amplifying its associated mortality risk at the population level. The association between relative sarcopenia and mortality is attenuated in persons with higher FMI.